Evaluating the financial performance of a sample of banks operating in the Kurdistan Region - Iraq for the period (2009-2019) - Ahmed, Younis Ali; Zahir, Wrya Muhammad (Journal of University of Human Development, 2022)
The performance appraisal process is one of the main objectives of the organization, and performance is one of the main factors and components that the organization relies on to measure success or failure. The financial analysis of bank balances is a clear reflection of the reality of the financial position of these banks, where the analysis of financial banking activity contributes to clarifying the weaknesses in the performance of banks and building an appropriate model for developing banking performance in banks in general and banks in particular, the research seeks to achieve the goal of evaluating financial performance For a sample of banks operating in the Kurdistan Region - Iraq for the period (2009 - 2019) by relying on the most important criteria and main indicators in evaluating financial performance and in order to achieve the goal of the research, it was relied on the descriptive-analytical comparative approach based on advanced standard methods and financial analysis and economic based on data obtained from annual reports issued by banks (research sample). It was found from the research and analysis and through the indicators that were used that there are large fluctuations in the annual financial statements of the banks and that the level of performance was not stable in the banks from one period to another due to the unstable financial and political conditions, as well as the weakness of the policies followed by some banks in some years in addition to the That and through the practical side, the research also reveals that according to the net profit margin ratio indicator (the United Investment Bank in the first place, the Iraqi Investment Bank in the second place, and the National Bank of Iraq in the third place), while these arrangements differ according to the type of indicators that must Those banks must work to achieve stability in banking activity and financial performance by raising competitiveness on the one hand and working to raise the level of direct and indirect investment competencies..